2018
DOI: 10.1016/j.ajog.2018.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Amnion epithelial cell–derived exosomes induce inflammatory changes in uterine cells

Abstract: In vitro, amnion epithelial cell exosomes lead to an increased inflammatory response in maternal uterine cells whereas placental cells showed refractoriness. Fetal cell exosomes may function to signal parturition by increasing maternal gestational cell inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 92 publications
4
77
0
Order By: Relevance
“…Recently, Emily E. Hadley et al demonstrated that hAESC-released exosomes under control and oxidative stress conditions were taken up by myometrial, decidual, and placental cells. The exosomes from both conditions significantly increased inflammatory mediators (IL-6, IL-8, and PGE2) and activated NF-kB in maternal cells, indicating that hAESC exosomes are a novel paracrine mechanism of fetal–maternal communication [ 145 ]. In terms of preclinical treatment with hAESC exosomes, researchers presented strong evidence on wound healing and fibrosis.…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
“…Recently, Emily E. Hadley et al demonstrated that hAESC-released exosomes under control and oxidative stress conditions were taken up by myometrial, decidual, and placental cells. The exosomes from both conditions significantly increased inflammatory mediators (IL-6, IL-8, and PGE2) and activated NF-kB in maternal cells, indicating that hAESC exosomes are a novel paracrine mechanism of fetal–maternal communication [ 145 ]. In terms of preclinical treatment with hAESC exosomes, researchers presented strong evidence on wound healing and fibrosis.…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
“…Labor is considered a state of systemic [15‐19] and local [20‐31] physiological inflammation [32‐35]. The latter concept is supported by consistent evidence showing that labor is characterized by an increase in cellular and soluble inflammatory mediators in the cervix [32,36‐48], myometrium [37‐38,40,49‐52], chorioamniotic membranes [38,40,53‐59], and decidual tissues (i.e. maternal–fetal interface) [38,40,53‐54,57,60‐63].…”
Section: Introductionmentioning
confidence: 99%
“…According to their diameter, EVs can be classified into two general subgroups: 1) small EVs (<200nm), and 2) medium/large EVs (>200 nm) [10]. Recent studies have identified EVs as critical players in intercellular communication under various physiological and pathological conditions such as neurodegenerative diseases, cancer, preterm birth, angiogenesis, immune responses, and viral infections [3,[13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%